Self-Care for Department Chairs and Faculty Members - Jeff Buller (Academic Chairpersons Conference Proceedings, 2022)
High rates of burnout and attrition among academic leaders and faculty members have led many colleges and universities to launch self-care programs. No longer regarded merely as a luxury, these programs have increasingly come to be regarded as essential components of a comprehensive professional development program. This presentation guides participants through best practices in their own self-care as well as strategies for developing a self-care program within their own departments.
Keywords: self-care; department chair; faculty attrition; burnout; best practices